Analisis Ekuitas Pemerintah Pusat - Yulistria Anggraini; Muhammad Irfan Rizaldi; Haryo Adik (Jurnal Syntax Admiration, 2024)
This study is prepared to analyze the causes of the declining trend in central government equity and further identify steps that the Government can take in anticipating the decline in equity. This research was conducted using descriptive analysis methods by analyzing trends in financial statements and comparing with policies and regulations that occurred in the reporting year so that it could not present further information about the reasons or considerations of the Government related to a policy that could increase / decrease equity significantly. As a result, this policy involves a formulation strategy with prudential and planned principles, especially in medium-term fiscal policy. The impact includes an increase in financing expenditures to cover the budget deficit, especially in operational expenditures.